A Comparative Study of Mean Platelet Volume in Diabetic Population With and Without Vascular Complication - Ajantha Swamy Vasudhevan; Dhivya Mohan Sumathi; Ashwath Kumar Chinnaraju Selvakumar; Rajabalaji Rajabalaji (Universitas Nahdlatul Ulama Surabaya, 2023)
Diabetes mellitus leads to long-term complications involving multiple organs and systems of the human body. Among the list of complications, a relatively vascular complication increases the morbidity of the condition. Patients with diabetes mellitus are influenced by various factors like hyperglycaemic state, insulin resistance, oxidative stress, and metabolic condition like obesity, and all the mentioned conditions also present with platelet hyperactivity. Mean platelet volume (MPV) can be used as one of the laboratory parameters to know the function and activation of the platelets, which reflects the vascular profile of the patient. So, the present study compares the values of mean platelet volume among the diabetic groups to determine the relation between the vascular complication and the mean platelet volume. This study was conducted with 90 participants, who were divided into three groups. Group A is non-diabetics, group B is type 2 Diabetics, and Group C is type 2 Diabetics with vascular complications and MPV. On analyzing the statistical mean value of mean platelet volume, group B's (type 2 diabetics) value was higher than group A's (non-diabetics) and statistically significant with a p – value of 0.001. Similarly, the mean value of group C (type 2 diabetes with complications) was higher than group B (type 2 diabetics) and statistically significant with a p – value of 0.049 in the diabetics with and without vascular complications. On comparing the MPV of different study groups, the MPV is higher in the diabetic group with complicatiosn compared with the diabetics without complications.